SOCIAL CAPITAL AMONG AGEING RESIDENTS OF HOUSING COMPLEXES IN SUBURBAN TOKYO: THE CASE OF HARAICHI-DANCHI AND OYAMADAI-DANCHI IN AGEO CITY - Nordin, Nadhirah; Nakamura, Hitoshi (PLANNING MALAYSIA, 2018)
Globally, developed nations such as Japan are currently facing an ageing population. The health and social care system in the living environment for the elderly population in Japan must engender strong social ties and social networks that can connect the elderly people and promote active ageing. This research aims to identify the extent of social capital among the ageing population in Haraichi-danchi and Oyamadai-danchi, which are housing complexes located in Ageo City, a suburb of Tokyo. This article focuses on residents in the 60s and 70s age groups. A questionnaire survey was conducted and was divided into three parts which include the basic attributes of the residents, the elements of bonding social capital and bridging social capital. Then, cross-tabulations were done between the age groups and both the social capital categories. Next, chi-square and further post-hoc analyses were conducted to determine the strongest association between the variables. The results show a significant association between the 60s and 70s age groups for both bonding and bridging social capital. The variation of results may be influenced by the physical environment of the housing complexes in which they are currently living.